Application of Iron Oxide Nanoparticles in the Diagnosis and Treatment of Neurodegenerative Diseases With Emphasis on Alzheimer’s Disease - Luo, Shen; Ma, Chi; Zhu, Ming-Qin; Ju, Wei-Na; Yang, Yu; Wang, Xu (Frontiers in Cellular Neuroscience, 2020)
Neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease and amyotrophic lateral sclerosis, are of unknown etiology, unfavorable prognosis and the treatments toward them are less effective. Such disease usually develops in the aged people, and the early clinical manifestations are atypical, resulting in difficulty in early diagnosis. Recently, nanomedicine has aroused considerable attention for diagnosis and therapy of central nervous system diseases since it can integrate targeting, imaging and therapy in one system. In this review, we summarize the application of iron oxide nanoparticles in the diagnosis and treatment of neurodegenerative disease, with emphasis on iron oxide nanoparticles as MRI contrast agents and drug carriers in AD.